2021
DOI: 10.1002/smll.202105724
|View full text |Cite
|
Sign up to set email alerts
|

Breathable Artificial Interphase for Dendrite‐Free and Chemo‐Resistive Lithium Metal Anode

Abstract: A dendrite‐free and chemically stabilized lithium metal anode is required for extending battery life and for the application of high energy density coupled with various cathode systems. However, uneven Li metal growth and the active surface in nature accelerate electrolyte dissipation and surface corrosion, resulting in poor cycle efficiency and various safety issues. Here, the authors suggest a thin artificial interphase using a multifunctional poly(styrene‐b‐butadiene‐b‐styrene) (SBS) copolymer to inhibit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The tilt‐view SEM image also confirmed that the SPF could accept such high amounts of Li metal as the functional host over the theoretical thickness of Li metal deposition (5 μm at the electrodeposition of 1 mAh cm −2 ) in Figure 3h because the PAV layer (30 μm), consisting of ionic polymers, densely stacked Li metal through bottom‐up accumulation, and SBS layer (10 μm) as an elastic barrier on top were flexibly controlled by stretching the polymer structure and blocking the Li penetration and potential of Li dendrite across the SBS layer. [ 41 ] Furthermore, cross‐section SEM images of Cu@SPF–Li showed the different amounts of Li electrodeposition to confirm the bottom‐up growth mechanism of the Li metal anode (Figure S8, Supporting Information). The densely packed Li with reasonable thickness was deposited from the bottom and gradually filled the void space in the host.…”
Section: Resultsmentioning
confidence: 93%
“…The tilt‐view SEM image also confirmed that the SPF could accept such high amounts of Li metal as the functional host over the theoretical thickness of Li metal deposition (5 μm at the electrodeposition of 1 mAh cm −2 ) in Figure 3h because the PAV layer (30 μm), consisting of ionic polymers, densely stacked Li metal through bottom‐up accumulation, and SBS layer (10 μm) as an elastic barrier on top were flexibly controlled by stretching the polymer structure and blocking the Li penetration and potential of Li dendrite across the SBS layer. [ 41 ] Furthermore, cross‐section SEM images of Cu@SPF–Li showed the different amounts of Li electrodeposition to confirm the bottom‐up growth mechanism of the Li metal anode (Figure S8, Supporting Information). The densely packed Li with reasonable thickness was deposited from the bottom and gradually filled the void space in the host.…”
Section: Resultsmentioning
confidence: 93%
“…6(a), and a pair of typical cathodic and anodic peak reflected a reversible couple redox of Fe 3+ /Fe 2+ . 61 Subsequently, the peak intensity of the insertion gradually increases with an increase in the scanning rates, indicating the fast kinetics of redox reaction at the electrode interface. Moreover, the difference in the current response values of each anodic peak is attributed to the de-intercalation of Li + in the artificial SEI.…”
Section: Resultsmentioning
confidence: 97%
“…[40,[191][192][193][194][195][196] Additionally, the flexible polymer can accommodate the volume change at the electrodes to alleviate damage to the electrolyte. [197,198] The overall performance of the layered electrolyte can be adjusted by combining layers with different properties. Because of the enhanced ion-conduction behavior, many of the single-layered composite electrolytes mentioned above are potential candidates for improving interfacial properties in multi-layer designs.…”
Section: Sandwich Layersmentioning
confidence: 99%